A Case of SAPHO Syndrome Complicated by Uveitis with Good Response to Both TNF Inhibitor and JAKinib - Baisya, Ritasman; Gavali, Meghna; Tyagi, Mudit; Devarasetti, Phani Kumar (Case Reports in Rheumatology, 2023)
Introduction. SAPHO (synovitis, acne, pustulosis, hyperostosis, and osteitis) syndrome is a rare autoinflammatory condition describing the constellation of inflammatory skin, bone, and joint manifestations which result in diagnostic difficulty and therapeutic challenge. Case. Here, we present a case of a young male diagnosed with SAPHO syndrome with osteoarticular and cutaneous involvement from an early age in his life. He suffered diagnostic challenges for a long time and was hence inadequately treated. He had minimal response to conventional DMARDs but showed excellent response to TNF inhibitor (adalimumab). Later, he defaulted treatment and presented with acute anterior uveitis which was also dramatically improved with adalimumab and tofacitinib although financial constraint was always an issue for the patient. Conclusion. The uniqueness of this case was that the patient had a multiorgan involvement including osteoarticular system, skin, and eye. Both TNFi (adalimumab) and JAKinib (tofacitinib) had a good response to all organs with a net improvement in the quality of life of this patient.